Factors Influencing the Reporting Time of Online-Based Recording and Reporting Systems in Public Health Center of Semarang City (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2019)
ABSTRACT The target of timely reporting of SP3 online in Semarang City in the first quarter of 2017, amounted to 72% of Public Health Centers on time. Quarter II of 2017 was 62%. This is not in accordance with the target set by the Semarang City Health Office, which is 80%. The purpose of the study was to determine the factors that influence the timeliness of monthly SP3 reporting in Semarang City. This is an observational analytic research with case-control design. The sample set was 14 cases and 14 controls. The research instrument used was structured questionnaire. The results showed age factor (p value = 0.018; OR = 10.8), incentive (p value = 0.023; OR = 9.1), workload (p value = 0.008; OR = 13.4), leader support (p value = 0.008; OR = 15), supporting facilities (p value = 0.033; OR = 13) influenced the timeliness of SP3 reporting and years of service factor (p value = 0.7; OR = 1.8), computer skills (p value = 0.55; OR = 2.07), education (p value = 1; OR = 1.4), job training (p value = 0.5; OR = 2.07), and co-worker support (p value = 0.02; OR = 2.5) had no influence on the timeliness of SP3 reporting. ABSTRAK Target ketepatan waktu pelaporan SP3 online Puskesmas Kota Semarang triwulan I tahun 2017, sebesar 72% puskesmas tepat waktu. Triwulan II tahun 2017 sebesar 62%. Hal ini tidak sesuai dengan target yang ditetapkan oleh Dinas Kesehatan Kota Semarang, yaitu 80%. Tujuan penelitian untuk mengetahui faktor yang mempengaruhi ketepatan waktu pelaporan Sistem Pencatatan Puskesmas (SP3) Bulanan Kota Semarang. Jenis penelitian adalah observasional analitik dengan rancangan case control. Sampel yang ditetapkan sebesar 14 kasus dan 14 kontrol. Instrumen penelitian berupa kuesioner terstruktur. Hasil menunjukkan faktor umur (p value=0,018; OR=10,8), insentif (p value=0,023; OR=9,1), beban kerja (p value=0,008 ; OR=13,4), dukungan pimpinan (p value=0,008; OR=15), fasilitas pendukung (p value=0,033; OR=13) mempengaruhi ketepatan waktu pelaporan SP3 dan faktor masa kerja (p value=0,7; OR=1,8), kemampuan teknik komputer (p value=0,55; OR=2,07), pendidikan (p value=1; OR=1,4), pelatihan kerja (p value=0,5; OR=2,07), dan dukungan rekan kerja (p value=0,02; OR=2,5) tidak mempengaruhi ketepatan waktu pelaporan SP3.